Interpreting how others interpret it: Social value of public information - Alia Gizatulina (Center for Economic Studies and ifo Institute (CESifo), 2012)
This paper studies the social value of public information in environments without common knowledge of data-generating process. We show that the stronger is the coordination motive behind agents behaviour, the more they would like to interpret private or public signals in the way that they suspect others are doing it. Consequently, the negative impact of public communication noted by Morris and Shin (2004) can be amplified if agents have doubts whether others take the public signal too literally and/or are too inattentive to their private signals. The social welfare increases when each agent evaluates the precision of public signal correctly but believes that others did not understand the public signal at all, which suggests that there is a scope for the central bank to 'obliterate' its communication in a specific way, by making it, e.g., sophisticated and technical.
Keywords: D82; E58; 330; central bank communication; transparency; common p-belief; coordination game; higher-order uncertainty